Systematic Review on Financial Education in the Primary Educational Context - Ferrada, Cristian; Díaz Levicoy, Danilo.; Puraivan, Eduardo; Lizana, Alexis (Corporacion Universitaria Lasallista, 2022)
Introduction: this research presents the results of a systematic literature review, following the PRISMA statement, on financial education in the context of primary education. Objective: to analyze through bibliometric and qualitative indicators in the SCOPUS database the state of financial education in the first education. Materials and Methods: with a longitudinal and descriptive design, bibliometric indicators are analyzed complemented with a qualitative analysis of elements that we want to make known, due to the coverage they provide and their scope in social sciences and humanities, the SCOPUS database was analyzed until the year 2020, following the elements established in the PRISMA statement. Results: the initial search yielded 170 articles, where 16 were left for study. Once the articles were analyzed according to the 10 evaluation criteria, it was found that financial education programs have, on average, considerable impacts on financial knowledge, like educational interventions in other domains. Conclusion: the value of the study is to enhance the construction of existing knowledge on financial education in primary education, contributing to elucidate its complexity and application that transits from the multidisciplinary to the contextualized, together with the idea of increasing reinforcement in the first years of schooling, since it generates positive effects on financial behaviors among students after participating in intervention programs
Revisão Sistemática sobre educação financeira no contexto da escola primária
Revisión sistemática sobre educación financiera en el contexto educativo primario
Keywords: Financial education; Primary education; Systematic review